“I am worried about the quality of my work…” EFL students’ voices on critical thinking skills - Fajaryani, Nunung; Habibi, Ibnu; Handayani, Reli; Failasofah, Failasofah; Abrar, Mukhlash; Ali, Rd. M. (Universitas Jambi, Indonesia, 2026)
Writing a thesis is a complex academic process that requires strong critical thinking skills. Consequently, many graduate students struggle to apply critical thinking during thesis writing. This study aims to explore EFL graduate students’ challenges and strategies in developing critical thinking skills in writing theses at Universitas Jambi. A qualitative case study design was employed, involving semi-structured interviews with four Master of English Education students who met the study’s inclusion criteria. The findings reveal three major categories of challenges: personal competence challenges (time management and workload balance), linguistic challenges (structuring and grammar, English proficiency, and source management), and psychological challenges (low motivation, lack of confidence, and writing anxiety). To address these challenges, students employed various strategies, including technological support such as AI and writing tools, time management practices, citation and resource management, and writing practice supported by supervisors and peers.